Awareness of MRSM's students towards accountancy as a profession / Mohamad Azmi Nias Ahmad - Nias Ahmad, Mohamad Azmi (Faculty of Accountancy, 2004)
This study is taken to investigate the Maktab Rendah Sains MARA's (MRSM) student's awareness towards accountancy as a profession. The objectives of this study are to identify factors that attract students in choosing the subject Principle of Accounts (PA) in the Sijil Pelajaran Malaysia (SPM) examination and to examine their awareness of accountancy as a profession. The study found out that most of the students chosen PA on their own. The study also indicated that the students choose PA subject because they have interest in the subject. Overall, the findings show that MRSM students have a low level of awareness towards accountancy as a profession.